Modern view on the rationale for way to prevent early neonatal infection - Gaidai, N. V.; Syusyuka, V. H.; Deinichenko, O. V.; Гайдай, Наталія Вікторівна; Сюсюка, Володимир Григорович; Дейніченко, Олена Валеріївна (My University, 2022)
For the fetus, the source of infection of any etiology is a pregnant woman in whom the disease can manifest itself with clinical symptoms or be in a latent form. There is a close link between the colonization of the mother's organism and her child. The frequency of infection during vaginal delivery composes 50-60%. [1] Purpose: the reason for writing this work was the necessity to analyze the causes of early neonatal infection cases in the maternity hospital and substantiate the main ways of preventing it. For this, we carried out a retrospective clinical and statistical analysis of 49 case histories and childbirth histories, newborns histories in the maternity hospital № 3 (Zaporizhzhia), who were diagnosed with intrauterine infection, intrauterine pneumonia within 24-48 hours. These newborns, due to the deterioration of their condition, were transferred by the children's intensive care team to the intensive care unit of the city children's clinical hospital № 5 (Zaporizhzhia), where they were examined and the clinical diagnosis was clarified.